2012
DOI: 10.1136/oemed-2011-100468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic stray fields from a 7 Tesla MRI scanner on neurocognition: a double-blind randomised crossover study

Abstract: Neurocognitive functioning is modulated when exposed to movement-induced TVMF within an SMF of a 7 T MRI scanner. Domains that were affected include attention/concentration and visuospatial orientation. Further studies are needed to better understand the mechanisms and possible practical safety and health implications of these acute neurocognitive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…No significant effects on cognitive function were found at any field strength or condition [35 • ]. In contrast, studies by the group of De Vocht showed some small but significant effects on attention/concentration and visuospatial orientation when the subject was positioned in the stray field of a 7 T scanner both when stationary and also after moving their head [36,37]. Bearing in mind the recent studies, discussed previously, on nystagmus, it would be interesting to investigate whether this could explain the observed cognitive effects in the visuospatial and attention/concentration domain, and to replicate the possible relation between nystagmus and these cognitive effects in a magnetic field free environment during vestibular activation [38].…”
Section: Biological Effects Of the Main Magnetic Field Strengthmentioning
confidence: 83%
“…No significant effects on cognitive function were found at any field strength or condition [35 • ]. In contrast, studies by the group of De Vocht showed some small but significant effects on attention/concentration and visuospatial orientation when the subject was positioned in the stray field of a 7 T scanner both when stationary and also after moving their head [36,37]. Bearing in mind the recent studies, discussed previously, on nystagmus, it would be interesting to investigate whether this could explain the observed cognitive effects in the visuospatial and attention/concentration domain, and to replicate the possible relation between nystagmus and these cognitive effects in a magnetic field free environment during vestibular activation [38].…”
Section: Biological Effects Of the Main Magnetic Field Strengthmentioning
confidence: 83%
“…Similarly, for patients, unpleasant effects (dizziness and vertigo, for example, but also tachycardia and sweating), some of which are related to the static field, are reported more often during imaging using 7 T systems than with 1.5 T systems [9]. Some of these reported effects may be related to adverse effects on visual perception, spatial orientation, visuomotor performance, working memory, and attention, measured in controlled trials [10][11][12][13]. Experimental studies similarly show that exposure to the static magnetic field has a direct negative, but temporary, effect on the vestibular system [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Current literature suggests that these symptoms have an acute and transient nature,10 16–18 and many of these arise when people move through the spatial gradients in the static magnetic stray field outside the MRI scanner, resulting in exposure to low-frequency TvMFs 14 17 18. In only a few studies were symptoms assessed in a (semi-)objective way, either by blinding subjects to the exposure condition, or by making inquiries about symptoms during the work day in general as opposed to specifically relating it to MRI or SMF exposure 8 15 17 19. Furthermore, in only a few studies was symptom occurrence related to different exposure conditions using statistical tests 8 9 14 15 20.…”
Section: Introductionmentioning
confidence: 99%